Pengaruh Literasi Keuangan, Life Style, dan Locus Of Control Terhadap Perilaku Pengelolaan Keuangan Mahasiswa Ekonomi Syariah Febi Angkatan 2019 - rahmawati, rahmawati; Harjoni, Harjoni; Nola, Sity Lutfia (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2024)
This study aims to analyze the effect of financial literacy, Life Style, and Locus Of control on the financial management behavior of FEBI students class of 2019 at IAIN LHOKSEUMAWE. This type of research is quantitative using primary data obtained through distributing questionnaires, the population in this study were students majoring in sharia economics FEBI IAIN LHOKSEUMAWE class of 2019. The sample used in this study was 60 respondents. The data was processed using statistical program for social science (SPSS) software. The results of this study indicate that financial literacy has no significant effect on student financial management behavior. Life Style variables have no effect on student financial management behavior. Locus Of control variables have a significant effect on student financial management behavior and Financial Literacy, Life Style, and Locus Of Control simultaneously affect student financial management behavior.